Indigenous Identity Formation in Rajan Mukarung’s Damini Bhir - Khadka, Kul Bahadur (Nepal Journal of Multidisciplinary Research, 2026)
Background: Indigenous texts in Nepal have been analysed largely through sociological, postcolonial and feminine lenses, however, lived socio-cultural practices and experiences, ethical values and communal roles have not been adequately explored. This study attempts to examine how Rajan Mukarung’s Damini Bhir articulates identity formation of the Rai community, focusing on the indigenous aesthetic systems of collective activism and adaptive capability to sustain. Methods: Employing a qualitative research design based on indigenous aesthetic methodology and theoretical knowledge of American scholar Steven Leuthold, the research makes textual analysis to identify various aesthetic qualities which vitalize the text for exposing indigenous integrity and identity. Results: The analysis demonstrates that indigenous aesthetics differs from the Western concepts of aesthetics and that the indigenous aesthetic phenomena deep-rooted in the text foreground resistance, relationality, kinship, memory, and judicious negotiation between tradition and modernity. Conclusion: Overall, the findings suggest that indigenous aesthetic systems rather than Western aesthetic phenomena function in the text for the formation of indigenous identity. Novelty: Based on indigenous aesthetic systems as a theoretical framework, the study might contribute to the genre of indigenous literature and criticism as it is opting for using indigenous aesthetic approaches in the interpretation of a contemporary literary text.